(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2014)
Little knowledge exists about the degree of source, sink and source: sink limitations on mean seed weight in oilseed rape (Brassica napus L.). The objective of this work was to analyze the nature and magnitude on seed weight response to assimilate availability during the effective seed-filling period in oilseed rape. Three Argentinean varieties, Eclipse, Impulse, and Master, were grown under field conditions, and at the beginning of the effective seed filling period, a broad range of source: sink manipulation combinations were produced. Source manipulations consisted of two incoming radiation (R) level reductions: 0% (Rn) and 50% (Rs) combined with three different sources: sink treatments were applied: C, control; PR, 50% pod removal, and D, 100% defoliation. Rs significantly reduced yield (15%) and MSW (12%) with respect to Rn, without significant effects on the rest of the sub yield components. Source:sink manipulation treatments significantly affected all yield components. PR diminished yield by 29%, reducing ca. 40% seeds pl-1 by reductions pods pl-1 (41%) with respect to Rn, whereas PR increased MSW by 19%, counterbalancing the reduction in seeds pl-1 and thereby in yield. When considering different seed positions along the main raceme, Rs reduced MSW by 12% independently of seed positions onto the raceme. On the contrary, PR increased MSW in average 17% with respect to C. Results reported here suggest that oilseed rape has source: sink co-limitation during the effective seed filling period, which is apparently higher than wheat and lower than maize. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21091 Int. J. Agril. Res. Innov. & Tech. 4 (1): 44-52, June, 2014